Kepentingan Pertanian Indonesia dalam Perdagangan Internasional - Apriyantono, Anton (Indonesian Journal of International Law, 2021)
Trade on Agriculture has been reformed since January 1995. It was a resultof Uruguay Round and staed on Agreement on Agriculture. However, its implementations have given negative aspects to developing countries. It was caused by the malfunction of specific protection mechanism. Besides, special and differential treatment, created by developed countries, is not implemented effectively. Accordingly, sector on Agriculture has been being negotiated since the Doha Round in 2001.